Characterizing observable COVID-19 controls in Pacific Northwest grocery stores. Issue 5 (4th May 2022) - Chan, Allen; Errett, Nicole A.; Srikanth, Pranav; Baker, Marissa G.
Abstract: Utilizing a longitudinal, observational study, grocery store health and safety controls implemented during the COVID-19 pandemic across stores in two cities were characterized. Sixteen stores between Seattle, WA (n = 9) and Portland, OR (n = 7) were visited monthly by the study team from May 2020 to January 2021, and observations of controls were recorded using a standardized checklist in REDCap. The checklist included questions on the presence or absence of controls such as physical barriers, social distancing markers, required masking of customers, cleaning of check-out stands, and closures of store areas. Descriptive analyses were conducted to determine the proportion of stores with a certain control each month. Mixed-effects logistic regression was used to explore how controls changed over time, and whether differences were observed between cities or by income of the area the store serves. Source control (e.g., mask requirements) and engineering controls (e.g., physical barriers at checkout) were the most common and consistent controls observed across stores and over the study period. Controls such as having special hours for vulnerable populations, demarcations on aisles for directionality, and cleaning check-out stands between customers varied significantly over time ( p < 0.05 in the mixed-effects model). Having an employee present to clean baskets and carts, as well as physical barriers between self-checkouts, were significantly more common in stores in areas above the median income ( p < 0.05 in the mixed-effects model). To best protect workers and shoppers from infectious agents, controls should be evidence-based, consistently implemented across grocery stores, and coupled with administrative practices and policies to promote worker wellbeing.